1994
DOI: 10.1093/jn/124.5.754
|View full text |Cite
|
Sign up to set email alerts
|

Viscous Indigestible Polysaccharides Reduce Accumulation of Pentachlorobenzene in Rats

Abstract: To investigate an effect of indigestible polysaccharides (cellulose as control, sodium alginate, guar gum or lambda-carrageenan) on the accumulation of pentachlorobenzene, male Sprague Dawley rats were fed experimental diets containing 5 g/100 g of these polysaccharides for 2 wk. They were then given orally 80 mumol (20 mg) of pentachlorobenzene along with their respective diets and the residual pentachlorobenzene was determined after 7 d. The ingestion of the viscous indigestible polysaccharides resulted in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 21 publications
1
22
0
1
Order By: Relevance
“…As shown in Table 1, the amounts of epididymal and perirenal fat tissue in the alginate and fish oil groups were lower than those in the control group. The results are consistent with our previous reports that feeding dietary fiber and fish oil to rats reduces the total content of fat in the body (3)(4)(5)(6)(7). It is widely recognized that fat tissue has an important role in the storage of drugs or xenobiotics in the body.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…As shown in Table 1, the amounts of epididymal and perirenal fat tissue in the alginate and fish oil groups were lower than those in the control group. The results are consistent with our previous reports that feeding dietary fiber and fish oil to rats reduces the total content of fat in the body (3)(4)(5)(6)(7). It is widely recognized that fat tissue has an important role in the storage of drugs or xenobiotics in the body.…”
Section: Resultssupporting
confidence: 92%
“…It easily crosses the gastrointestinal wall and rapidly disappears from the blood , being ex haled unchanged or accumulated in tissues via the blood stream and metabolization (17,22,23). TCE is more rapidly metabolized than PECB or HCB, which were used in our previous studies (3)(4)(5)(6)(7). In those studies, we found that PECB residues in the body were much lower in amount in rats fed viscous indigestible polysaccharides (3,4) and fish oil (5,6).…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…13 Also various organic and inorganic chemicals are possibly bound to dietary fiber in the GIT and quickly excreted in the stools. 14,15 Generally the residual pyrethroid levels in different matrices are determined using chromatographic methods, mainly gas chromatography with electron-capture 5 (GC-ECD) or mass spectrometry detection (GC-MS), [16][17][18] and liquid chromatography has also been employed in some studies. 19,20 Nevertheless electron-capture detection (ECD) is the most frequently selected system for the determination of pyrethroid residues, being especially suitable for the determination of those pyrethroids which possess a chloro atom (cypermethrin, permethrin), bromo atom (deltamethrin), fluoro atom (cyhalothrin), or chloro and fluoro atoms (fluvalinate) in their structure.…”
Section: Introductionmentioning
confidence: 99%
“…Bead-type of alginate gel can be easily prepared in one step without any harsh conditions for living cells inside the beads, and therefore, they have been extensively used for the immobilization of various biomolecules: immobilization of living cells in a fermentor; immobilization of hybridoma cells to produce monoclonal antibodies; and entrapment of mammalian cells for the implantation of artificial organs. [1][2][3][4][5][6][7] Alginate also has some useful characteristics that can be exploited for pharmaceutical purposes. In particular, the formation of a net-like lattice between the cations and the alginate within the gel is responsible for the slow release of the embedded drugs, which can be used for the development of alginate-based drug delivery systems (DDS).…”
mentioning
confidence: 99%